Digital Transformation in the Education Sector: The Role of MIS Integration in Driving Operational Efficiency and Competitive Advantage - Ulya Amelia; Evitha Soraya; Cynthia Mayang Sari (Universitas Negeri Jakarta, 2025)
Background: Background: The rapid digital transformation driven by Industry 4.0 and Society 5.0 has placed significant pressure on educational institutions to modernize their operations. While Management Information Systems (MIS) are widely recognized as essential for centralizing and streamlining institutional processes, many schools continue to rely on fragmented, siloed systems that limit efficiency and strategic impact. Previous studies have largely focused either on individual perceptions of technology use or on student outcomes, leaving a gap in understanding how MIS integration holistically influences institutional performance.Purpose This study addresses that gap by examining the integration of digital technologies within MIS and its impact on both operational efficiency and competitive advantage in the education sector.Design/method/approach Using a qualitative, instrumental case study design, data were gathered from five Jakarta-based schools through interviews, observations, and document analysis.Results Findings indicate that moving from isolated systems to an integrated, cloud-based MIS enhanced efficiency across time, cost, and workflows, while also ensuring higher data accuracy and enabling evidence-based decision-making. These gains directly translated into stronger institutional reputation, improved stakeholder services, and greater organizational agility. Success was strongly supported by visionary leadership and comprehensive training, whereas resistance to change, technical glitches, and infrastructural limitations posed challenges.Contribution/value The study contributes a holistic, empirically grounded model that links MIS integration to both operational and strategic outcomes. By bridging theoretical potential with practical evidence, it offers valuable insights for educational leaders formulating digital transformation strategies.